State Of Road Safety on The Roads of Kazakhstan (Global Scientific Review, 2023)
In the process of work, theoretical studies were carried out on foreign practices in compiling reports on the state of road safety on the roads of foreign countries and their associations . In addition, an analysis of the state of road safety on public roads in Kazakhstan was carried out, the main factors determining the current state of accidents and trends in their changes over the past period were identified. Economic losses from road accidents were determined in accordance with the current methodology